If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (25) + (x + 15) = (3x + -10) 25 + (x + 15) = (3x + -10) Reorder the terms: 25 + (15 + x) = (3x + -10) Remove parenthesis around (15 + x) 25 + 15 + x = (3x + -10) Combine like terms: 25 + 15 = 40 40 + x = (3x + -10) Reorder the terms: 40 + x = (-10 + 3x) Remove parenthesis around (-10 + 3x) 40 + x = -10 + 3x Solving 40 + x = -10 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 40 + x + -3x = -10 + 3x + -3x Combine like terms: x + -3x = -2x 40 + -2x = -10 + 3x + -3x Combine like terms: 3x + -3x = 0 40 + -2x = -10 + 0 40 + -2x = -10 Add '-40' to each side of the equation. 40 + -40 + -2x = -10 + -40 Combine like terms: 40 + -40 = 0 0 + -2x = -10 + -40 -2x = -10 + -40 Combine like terms: -10 + -40 = -50 -2x = -50 Divide each side by '-2'. x = 25 Simplifying x = 25
| Y=-0.414(70)+106.55 | | -1(x+m)=3(x+9)-10 | | 3x+-4=x+2 | | -85=5(1-3x) | | 18-(3-2m)=3(m-5) | | 100[0.03(p+4)]= | | [3x]=-27 | | 6m+2(4-2m)=3(m+4) | | 3/8-5/6= | | 2v^2-11v-40=0 | | -(3w-2)-w=30 | | 3.5+32.1=4.9-10.1x | | 8(2n+5)=6(6n+4)+2 | | Factorx^2+2x+100=0 | | 25x+15=3x-10 | | log(y)=-3log(x) | | 27=-4x+7x-6 | | 15=8+.75x | | 5-3(4-2m)=4(m-3)-3 | | 5m+3(m-2)=6m-12 | | -2-7a=8-5a | | 5(2n+3)=8(6n+1)+4 | | -184=6-8(7-8n) | | -2m-13-8(m-4)=7m-(8m-3)-6m+1 | | 7m-(9-4m)=3(m-11) | | Y+3.9=11.8 | | -184=-8(7-8n) | | Y+3.9=11.8 | | 7m-(9-4m)=3(m-11) | | x^2+4x+2.2=0 | | -2m-13-8(m-4)=7m-(8m-3)-6m+1 | | -3d+-28=-40 |